Pengaruh Penggunaan Teknologi Digital terhadap Kemampuan Membaca Anak di Sekolah Dasar: A Systematic Literature Review - Pratama, Aprilyanti; Mahendra, Yasinta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The advancement of digital technology has significantly transformed the learning process in elementary schools, particularly in developing students’ reading skills. However, the integration of digital technology in basic literacy learning remains debated regarding its effectiveness, learning motivation, and the role of teacher and parental support. This study aims to analyze the influence of digital technology use on elementary students’ reading ability through a Systematic Literature Review (SLR) approach. Data were collected from twelve nationally indexed Sinta articles published between 2022 and 2025. The review process followed the PRISMA model, consisting of identification, screening, and thematic analysis based on each study’s focus. The synthesis results indicate that the use of digital media such as Canva, Literacy Cloud, digital comics, instructional videos, and read-aloud e-books consistently improves early reading skills, text comprehension, and students’ learning motivation. On the other hand, the success of digital technology utilization largely depends on teachers’ pedagogical design and parental supervision in managing screen time. This study concludes that digital technology has great potential to enhance elementary students’ reading literacy when implemented pedagogically, adaptively, and accompanied by character-based digital literacy reinforcement.